2020
DOI: 10.1371/journal.pone.0228948
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles isolated from patients undergoing remote ischemic preconditioning decrease hypoxia-evoked apoptosis of cardiomyoblasts after isoflurane but not propofol exposure

Abstract: Remote ischemic preconditioning (RIPC) can evoke cardioprotection following ischemia/ reperfusion and this may depend on the anesthetic used. We tested whether 1) extracellular vesicles (EVs) isolated from humans undergoing RIPC protect cardiomyoblasts against hypoxia-induced apoptosis and 2) this effect is altered by cardiomyoblast exposure to isoflurane or propofol. EVs were isolated before and 60 min after RIPC or Sham from ten patients undergoing coronary artery bypass graft surgery with isoflurane anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…However, it was suggested that RIPC increases endogenous plasma exosomes or microvesicles (possibly platelet-derived) [34] that can deliver signals to the myocardium and other tissues to provide protection against ischemia and reperfusion injury by a pathway involving TLR4 and protective heat shock proteins [34][35][36][37]. Of interest, Abel et al reported that extracellular microvesicles isolated from patients undergoing RIPC vs sham were associated with decreased hypoxia-evoked apoptosis of cardiomyoblasts after iso urane --but not propofol exposure [15,38]. Yu et al [39], in a rodent model, suggested that propofol blunts the cardioprotective effect of RIPC through its effect on the cardiac TRPV1 channel only if it is administered before RIPC, but not when propofol is given after RIPC [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was suggested that RIPC increases endogenous plasma exosomes or microvesicles (possibly platelet-derived) [34] that can deliver signals to the myocardium and other tissues to provide protection against ischemia and reperfusion injury by a pathway involving TLR4 and protective heat shock proteins [34][35][36][37]. Of interest, Abel et al reported that extracellular microvesicles isolated from patients undergoing RIPC vs sham were associated with decreased hypoxia-evoked apoptosis of cardiomyoblasts after iso urane --but not propofol exposure [15,38]. Yu et al [39], in a rodent model, suggested that propofol blunts the cardioprotective effect of RIPC through its effect on the cardiac TRPV1 channel only if it is administered before RIPC, but not when propofol is given after RIPC [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was suggested that RIPC increases endogenous plasma exosomes or microvesicles (possibly platelet-derived) 34 that can deliver signals to the myocardium and other tissues to provide protection against ischemia and reperfusion injury by a pathway involving TLR4 and protective heat shock proteins 34 – 37 . Of interest, Abel et al reported that extracellular microvesicles isolated from patients undergoing RIPC versus sham were associated with decreased hypoxia-evoked apoptosis of cardiomyoblasts after isoflurane – but not after propofol 15 , 38 . Yu et al 39 , in a rodent model, suggested that propofol blunts the cardioprotective effect of RIPC through its effect on the cardiac TRPV1 channel only if it is administered before RIPC, but not when propofol is given after RIPC 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic engineering approaches, which can be expensive and time-consuming, can only be used with EVs obtained from cell culture. It is necessary to use other methods to load therapeutic agents into EVs obtained directly from human plasma [ 41 , 42 , 43 , 44 ], adipose tissue [ 45 , 46 , 47 ], and breast milk [ 48 , 49 , 50 ]. Additionally, it may be challenging or impossible to implement genetic engineering approaches for EVs obtained from plants [ 51 , 52 ] and animal sources, such as bovine milk [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%